2007
DOI: 10.1071/fp06315
|View full text |Cite
|
Sign up to set email alerts
|

Gene families and evolution of trehalose metabolism in plants

Abstract: Abstract. The genomes of Arabidopsis thaliana L., rice (Oryza sativa L.) and poplar (Populus trichocarpa Torr. & A.Gray) contain large families of genes encoding trehalose-phosphate synthase (TPS) and trehalose-phosphatase (TPP). The class I subfamily of TPS genes encodes catalytically active TPS enzymes, and is represented by only one or two genes in most species. A. thaliana is atypical in having four class I TPS genes, three of which (AtTPS2-4) encode unusual short isoforms of TPS that appear to be found on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
210
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(218 citation statements)
references
References 67 publications
7
210
1
Order By: Relevance
“…Trees were created with the PHYML program (Guindon et al, 2005), implementing the WAG model of amino acid substitution (Whelan and Goldman, 2001) from a full-length alignment (excluding gaps). Consensus trees from 100 bootstrap runs are shown and agree well with those previously published for Arabidopsis; trees from Brachypodium proteins closely resemble those published for rice (Oryza sativa;Lunn, 2007).…”
Section: Phylogenetic Analysissupporting
confidence: 73%
See 1 more Smart Citation
“…Trees were created with the PHYML program (Guindon et al, 2005), implementing the WAG model of amino acid substitution (Whelan and Goldman, 2001) from a full-length alignment (excluding gaps). Consensus trees from 100 bootstrap runs are shown and agree well with those previously published for Arabidopsis; trees from Brachypodium proteins closely resemble those published for rice (Oryza sativa;Lunn, 2007).…”
Section: Phylogenetic Analysissupporting
confidence: 73%
“…This mechanism involves the pathway that synthesizes the nonreducing disaccharide trehalose. In Arabidopsis there are 21 genes that encode putative trehalose phosphate synthase (TPS) and trehalose phosphate phosphatase (TPP) genes (Avonce et al, 2006;Lunn, 2007). The trehalose pathway is ubiquitous in plants and it has been known that it is an indispensable component of plant development in seeds (Eastmond et al, 2002) and for vegetative development and transition to flowering (van Dijken et al, 2004) with trehalose 6-P (T6P) shown as the critical factor (Schluepmann et al, 2003).…”
mentioning
confidence: 99%
“…Expression studies in yeast revealed that they all have TPP activity, and promoter-GUS-GFP lines showed that each one has a tissue-specific expression pattern in Arabidopsis . In contrast to the large TPS and TPP gene families in Arabidopsis, trehalase is encoded by a single gene, AtTRE1 (Müller et al, 2001a;Lunn, 2007). Among the vascular plants, only a few desiccation-tolerant resurrection plants, such as Selaginella lepidophylla and Myrothamnus flebellifolius, accumulate substantial amounts of trehalose (Zentella et al, 1999).…”
mentioning
confidence: 99%
“…The synthesized trehalose can be hydrolyzed into two Glc monomers by the enzyme trehalase. Most genomes of higher plants contain elaborate trehalose biosynthesis gene families (Lunn, 2007;Avonce et al, 2010). The genome of Arabidopsis (Arabidopsis thaliana) contains 11 TPS genes (AtTPS1-AtTPS11) and 10 TPP genes (AtTPPA-AtTPPJ; Leyman et al, 2001).…”
mentioning
confidence: 99%
“…Interestingly, trehalases are not as widely distributed as the trehalose biosynthetic pathway, since trehalose-6-phosphate synthase/ phosphatases (TPS/TPP) are found in monera, protist, fungi, plant and the animal kingdoms (including vertebrates). [1][2][3] Trehalase sequence analysis (ref. 33; Table 1) unveiled the three major branches (Fig.…”
mentioning
confidence: 99%